Principle and theoretical background of pressure-retarded osmosis process - Sarper Sarp (Osmosis Engineering, 2021)
Pressure-retarded osmosis (PRO) uses a semipermeable membrane to control the osmotic mixing to generate renewable osmotic power from a salinity gradient. The main goal of a PRO system is to economically provide an appropriate amount of green energy. Furthermore, one of the key factors for a successful PRO system is the selection of a suitable draw solution that possesses a greater osmotic pressure than that of the feed solute to drag water through the membrane. Therefore quantifying the osmotic pressure and the extractable mixing energy is required. In this chapter, we discuss the general principles of PRO, before addressing modeling of the osmotic pressure associated with the osmotic power generation.